Dialogic literary argumentation in high school language arts classrooms : a social perspective for teaching, learning, and reading literature /: a social perspective for teaching, learning, and reading literature. (2019) - Bloome, David; Newell, George (George Edward), 1951-; Hirvela, Alan; (Professor of educational psychology), Lin, Tzu-Jung
No abstract available